On the Issue of Mobilization of Buddhist Theological School Students and Monastics for Military Rear Work during the First World War (1916–1917) (based on Materials from the State Archives of the Republic of Buryatia) - Bazar D. Tsybenov; Bair Ts. Gomboev (Монголоведение)
Introduction. Researchers have little studied some aspects of the requisition of Buryats for military rear work during the First World War. The question of conscription of students of Buddhist theological schools is a complex one. The aim of the study is to conduct an archival study of the details of the requisition process and the position of the Buddhist clergy of Eastern Siberia in relation to the mobilization of students. The authors solved the following problems: 1) analyze statistical data on conscript students and monks in the lists of datsans and local volosts; 2) monitor the interaction of the Buddhist clergy with regional and central authorities on issues of requisition; 3) determine the categories of students and monastics who have been released from military rear work; 4) study the role of requisitioned representatives of the Buryat Buddhist Church in helping lama healers in the Arkhangelsk region. Conclusions: despite the petitions of the Buryat Buddhist hierarchy to exempt students of Buddhist theological schools from military rear work, they, together with monastics, numbering 1,600 people, were sent to the regions of Arkhangelsk and Belarus. In addition to military and rear work, they provided assistance to lama healers. Some students were exempt for medical reasons, as well as workers and employees of enterprises working for national defense. Individual khuvaraks studying in Mongolia and Tibet were also exempt from requisition.